Thermal characterisation of rectangular cooling shapes in heat generating mediums - a three-dimensional investigation - Dirker, Jaco (Strojniški vestnik, 2005)
The optimum aspect ratios of uniformly distributed embedded rectangular cross-sectioned solid cooling inserts in a heat-generating medium are investigated. Numerical investigations were performed to determine and characterise how various geometric and thermal parameters determine these optimum shapes.
Keywords: generiranje toplote; strukture hladilne; metode eksperimentalne; prenos toplote; matematični modeli; termične lastnosti; kvader